2013
DOI: 10.1021/am400606y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Aerosol Jet Printing for High-Resolution, High-Aspect Ratio Silver Lines

Abstract: Aerosol jet printing requires control of a number of process parameters, including the flow rate of the carrier gas that transports the aerosol mist to the substrate, the flow rate of the sheath gas that collimates the aerosol into a narrow beam, and the speed of the stage that transports the substrate beneath the beam. In this paper, the influence of process parameters on the geometry of aerosol-jet-printed silver lines is studied with the aim of creating high-resolution conductive lines of high current carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
291
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(322 citation statements)
references
References 26 publications
9
291
0
Order By: Relevance
“…First, AJP produces much finer resolution. Mahajan et al defined the "focusing ratio" as the flow rate ratio of sheath gas flow rate to carrier gas flow rate [43]; they found that the printed line width decreases as the focusing ratio increases, while the standard deviation from run to run decreases, thus enabling a highly repeatable reduction in feature size. However, DIW with its submicron nozzle diameter enables even finer printing than AJP.…”
Section: Comparison Of Direct Write Methodsmentioning
confidence: 99%
“…First, AJP produces much finer resolution. Mahajan et al defined the "focusing ratio" as the flow rate ratio of sheath gas flow rate to carrier gas flow rate [43]; they found that the printed line width decreases as the focusing ratio increases, while the standard deviation from run to run decreases, thus enabling a highly repeatable reduction in feature size. However, DIW with its submicron nozzle diameter enables even finer printing than AJP.…”
Section: Comparison Of Direct Write Methodsmentioning
confidence: 99%
“…7 An alternative to the use of liquid inks has been developed in the last decade consisting in the direct writing with gas-phase coating techniques where an atomic vapor or nanoparticles dispersed in a carrier gas are deposited directly or through a shadow mask. 12 Direct writing from the gas phase is a low-cost and high-throughput technology suitable also for 3D substrates; 13 its widespread application is, however, hampered by the lack of acceptable adhesiveness on the substrate and electrical conductivity of the deposited species.…”
Section: 2mentioning
confidence: 99%
“…AJP is an excellent method for additive patterning of various kinds of electronically functional liquid inks, Figure 1 b. [ 3,10,15 ] By optimizing the carrier gas/sheath gas ratio, we controlled the minimum line widths in the range of 30 -50 µm (Figure 1 c). Figures 1 d-f display optical images of a discrete EGT, a completed complementary inverter, and a fi ve stage ring oscillator, respectively.…”
mentioning
confidence: 99%